Impact of integrated viral DNA on the goal to clear hepatitis B surface antigen with different therapeutic strategies - Lindh, Magnus; Rydell, Gustaf E; Larsson, Simon B (Current opinion in virology, 2018)
•Loss of hepatitis B surface antigen (HBsAg) from blood is a criterion for cure.•Current antiviral treatment controls replication but rarely achieves HBsAg loss.•Persistent HBsAg levels are likely due to expression from integrated viral DNA.•Therapies that also target integrated DNA are highly demanded. A hallmark of hepatitis B virus (HBV) infection is the presence of hepatitis B surface antigen (HBsAg) in the serum of patients. Sustained loss of HBV DNA and HBsAg from the blood are main goals for treatment, and considered as functional cure. It is rarely achieved with long-term nucleoside analogue treatment though, both because cccDNA, the template for viral replication, is not completely cleared, and probably also because hepatocytes with HBV DNA integrated into their chromosomes persist and continue to produce large amounts of HBsAg. Therefore, loss of HBsAg requires that both cccDNA and integrated DNA are cleared or their expression blocked. Recent data indicate that this may be achieved in some patients by stopping nucleoside analogue treatment, and that HBsAg-levels can be reduced by using specific interfering RNA. In the future, targeted degradation or disruption of HBV DNA might be possible using genome editing techniques such as CRISPR/Cas9.